2022
DOI: 10.1186/s12891-022-05160-9
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of geometric deformations of the lumbar disc during axial body rotations

Abstract: Background Quantitative data on in vivo vertebral disc deformations are critical for enhancing our understanding of spinal pathology and improving the design of surgical materials. This study investigated in vivo lumbar intervertebral disc deformations during axial rotations under different load-bearing conditions. Methods Twelve healthy subjects (7 males and 5 females) between the ages of 25 and 39 were recruited. Using a combination of a dual flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Recently, there have been reports on the in vivo kinematics of the lumbar spine, including the characteristics of intervertebral disc motion and deformation [14], the range of motion of the lumbar small joints [9], and the characteristics of inter spinous process motion [10]. These studies not only led to the study of in vivo kinematics of the lumbar spine but also set the framework for the method by which in vivo kinematics data of the lumbar spine can be obtained under physiological loads to ultimately provide reference data for explaining the occurrence, development, and changes in lumbar degenerative diseases, as well as guiding treatment (especially nonfusion treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been reports on the in vivo kinematics of the lumbar spine, including the characteristics of intervertebral disc motion and deformation [14], the range of motion of the lumbar small joints [9], and the characteristics of inter spinous process motion [10]. These studies not only led to the study of in vivo kinematics of the lumbar spine but also set the framework for the method by which in vivo kinematics data of the lumbar spine can be obtained under physiological loads to ultimately provide reference data for explaining the occurrence, development, and changes in lumbar degenerative diseases, as well as guiding treatment (especially nonfusion treatment).…”
Section: Discussionmentioning
confidence: 99%
“…In our published studies [ 23 , 26 ], the coupling translation part of intervertebral disc compression deformation and facet scoliosis were affected by an additional 10 kg load, while research on spinous process structure had no significant effect on load movement. This finding suggests that in spinal movement, the vertebral body and intervertebral joints conduct and limit spinal movement and bear most of the load.…”
Section: Discussionmentioning
confidence: 99%
“…The kinematic characteristics of the lumbar spine have been the focus of research. Previous studies on the lumbar spine are mainly focused on the anterior structures of the spine, such as the vertebral body [ 17 , 19 ], intervertebral disc [ 26 ], and facet joint [ 11 , 23 ]. A few scholars have focused on the spinous process, which can increase the firmness and stability of the spine [ 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Author details 1 Clinical Department of Orthopaedics, Tianjin Medical University, Tianjin, China. 2 Department of Spine Surgery, Tianjin Hospital, Jiefangnanlu 406, Hexi District, Tianjin, China.…”
Section: Open Accessmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors found the incorrectly direction of coupled lateral bending under 10 kg load during right rotation in Fig. 6 and herein make corrections of these errors.…”
mentioning
confidence: 97%